The Reality of Developing Innovative Thinking Skills in The Plastic Arts Curriculum from Point of View of Third-Grade Primary Teachers - Al-Balushi, Ruqaya Issa Mohammed (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the reality of developing innovative thinking skills in the plastic arts curriculum from the point of view of third-grade primary teachers in the Wilayat of Sohar, Sultanate of Oman. The study was based on the descriptive and analytical approach, and the study sample consisted of (30) teachers from public and private schools in the state of Sohar, who were chosen randomly during the second semester of the year 2020/2021 AD, and the study tool consisted of a questionnaire consisting of (15) items in three axes, namely: ( Originality, flexibility and fluency) and after making sure of the validity and stability of the tool, it was applied to the sample, The results of the study showed that the skill of originality and flexibility got an arithmetic average at the high level, and fluency obtained an arithmetic average at the intermediate level. The results also showed that there are no statistically significant differences at (0.05) attributable to the school classification variables (government - private) and the years of experience variable in the reality of developing innovative thinking in the plastic arts curriculum for third-grade primary teachers. In light of the results, the researcher recommended that female teachers of plastic arts be subjected to training courses and workshops in innovative thinking skills in the third primary grade. And the inclusion of innovative thinking skills in the artistic concepts, objectives, activities, evaluation and artistic works of the plastic arts curriculum from the early stages of the study; And adding electronic curricula and content in innovative thinking to the curricula of plastic arts for the third basic grade, and benefiting from the plastic arts classes in deducting a part of it in the work of workshops in the basics of drawing and coloring that help students to develop innovative thinking skills, enrich the curriculum with images of Omani heritage, and more broadly inculcate the values ​​of valid citizenship in the curricula. Fine Arts for the third year of primary school.